Simultaneous Estimation Of Nebivolol Hydrochloride And S-Amlodipine Besylate By High Performance Thin Layer Chromatography - ANILKUMAR SHARMA,; BHAVESH PATEL,; RAKSHIT PATEL, (International Journal of Pharma and Bio Sciences, 2010)
A simple, rapid, and reliable HPTLC method has been established for simultaneous determination of Nebivolol and S-Amlodipine in pharmaceutical dosage forms. Identification and quantification were performed on silica gel 60 F254 HPTLC plates, prewashed with methanol, with chloroform:toluene:methanol:glacialacetic acid, (5:2:3:0.1, v/v/v/v), as mobile phase. This system furnished compact bands for Nebivolol (Rf 0.48) and S-Amlodipine (Rf 0.33).Calibration curves were established showing the dependence of response (peak area) on the amount chromatographed. The validated linearity ranges were 500–2500 ng /spot (r2 = 0.9978) and 250–1250 ng/spot (r2 = 0.9972) for Nebivolol and S-Amlodipine, respectively. The spots were scanned at λ =271 nm. The suitability of this HPTLC method for quantitative determination of the compounds was proved by validation in accordance with the requirements of the ICH guidelines. The method was used for determination of the compounds in commercial pharmaceutical dosage forms. The method is simple, reproducible, accurate and can be used as a more economical alternative to other chromatographic techniques for routine quality control.